Using Mythic Structure of Campbell’s Monomyth to Analyze Spirited Away: A Heroine’s Journey - Meng-Hsuan Wu; Ya-huei Wang (Universitas Tidar, 2022)
This study intends to examine the stages of the hero’s journey based on the mythic structure of Campbell’s monomyth and use the monomyth to analyze how a ten-year-old girl, Chihiro, embarks on a journey to the supernatural world in Spirited Away. The study uses content analysis, a descriptive qualitative method, to analyze the monomyth: a departure–initiation–return journey covering seventeen stages. The monomyth involves metamorphoses and challenges that the heroine Chihiro encounters and explores her evolution during her transition to full autonomy in order to reach transformation and self-individuation. Chihiro, in order to rescue her parents, is destined to take the journey: to sink into darkness, the unconscious, and encounter her natural and primitive essence. By fighting against conflict or opposition, Chihiro, as a mythical heroine, completes her monomyth cycle and attains transformation and regeneration.